Socioeconomic typology of the municipalities of the wilaya of Saida -Capability approach- Typologie socioéconomique des communes de la wilaya de Saida -Approche par les Capabilités – - بن محمد, شريفة (جامعة مسيلة, 2018)
The wilaya of Saida knows inequalities of capabilities between these municipalities. Other way, the opportunities given by municipalities to residents are unfair. Therefore, they feel excluded from the development process. In this context, the actors of territorial development are called to reduce those inequalities. To complete this task, they need the development of methods for measuring to evaluate upstream and downstream situations. The objective of this paper is to make a typology of the municipalities of wilaya of SAIDA in terms of territorial capacity. For this, the use of the hierarchical ascending classification (HAC) method is propice because it makes it possible categories of municipalities with similar characteristics from the point of view of the variables selected. The results clearly show three groups of municipalities with different territorial capabilities depending on whether they are urban, semi urban or rural.
Keywords: Capability approache, HAC, territory ,development, disparities Jel code classification: I31, I39, R58